Unter die Lupe genommen:: Kompositorische Auseinandersetzungen mit Ludwig van Beethoven seit 2010 - Nonnenmann, Rainer (Die Musikforschung, 2022)
Beethoven enjoys an astonishing presence in contemporary musical life, although two hundred years separate him from our present. His mature works are considered “the foundation of modern music” (Hans-Joachim Hinrichsen 2019). However, their continued veneration and marketing has often led to a failure to recognise their potential for innovation, which once made them the new music of their time. Like “classical music” in general, Beethoven is frequently misunderstood as a self-evident exhibit in “The Imaginary Museum of Musical Works” (Lydia Goehr 1992). The tension between enduring modernity and growing historical distance makes Beethoven a central point of reference for contemporary composers. Since his 200th anniversary in 1970, numerous compositional explorations of his music have emerged, especially in the run-up to the 250th anniversary in 2020. Using a small selection of new instrumental works from the 2010s by Hans Zender, Johannes Schöllhorn, Frank Zabel, Johannes Quint, Vito Palumbo and others, this essay examines various ways of arrangements and recompositions which reflect on, update or analyse Beethoven’s music.